Intervals Between Bone Density Testing. (February 2014) - Reid, Ian R; Gamble, Gregory D
ABSTRACT There is a wide range of practices regarding times between bone density (BMD) measurements in osteopenic women. If decisions to treat osteoporosis are to be based on absolute fracture risk, then projections of fracture risk are a logical basis for determining appropriate intervals for BMD testing. Fracture risk depends mainly on age and BMD, and bone loss in older women is relatively constant at ∼1% annually, so it is possible to project fracture risk into the future and estimate when an individual's risk will approach the threshold for intervention. Modeling scenarios for a range of osteopenic baseline BMDs in 65‐year‐old women shows a remarkable consistency in the doubling time for Fracture Risk Assessment Tool (FRAX)‐assessed fracture risk: 5 to 6 years. This estimate is of immediate relevance to clinical practice in that it can be used to determine how long to wait before reassessing BMD and fracture risk in women whose other risk factors are stable. © 2014 American Society for Bone and Mineral Research.